2010
DOI: 10.14411/eje.2010.066
|View full text |Cite
|
Sign up to set email alerts
|

Ecological factors determining the density-distribution of Central European dragonflies (Odonata)

Abstract: Abstract. Habitat specificity is the most important factor affecting the regional distribution of dragonflies. Nevertheless, species with the highest specificity are not always the scarcest. Several important determinants of dragonfly density-distribution relationships were identified. Altitude preference and altitude range are significantly associated with dragonfly distribution. Some of the species that are habitat specialists but occur over a wide range of altitudes should be classified as rare but not enda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 44 publications
1
35
1
1
Order By: Relevance
“…In our study the species most closely associated with the latter factor (the highest correlations with Cordulia aenea, Aeshna juncea, Pyrrhosoma nymphula, Enallagma cyathigerum and Somatochlora mettalica) prefer higher altitude (see De Knijf et al, 2013). According to Harabiš and Dolny (2010) species that prefer higher biotopes are generally scarcer because there is less availability of water biotopes at higher than at lower altitudes. This is in agreement with results of our study which revealed that most species prefer springs at lower altitudes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study the species most closely associated with the latter factor (the highest correlations with Cordulia aenea, Aeshna juncea, Pyrrhosoma nymphula, Enallagma cyathigerum and Somatochlora mettalica) prefer higher altitude (see De Knijf et al, 2013). According to Harabiš and Dolny (2010) species that prefer higher biotopes are generally scarcer because there is less availability of water biotopes at higher than at lower altitudes. This is in agreement with results of our study which revealed that most species prefer springs at lower altitudes.…”
Section: Discussionmentioning
confidence: 99%
“…The relative importance of different factors in aquatic and terrestrial habitats during larval and adult life stages of odonates, respectively, is poorly understood (Remsburg and Turner, 2009). Despite relatively long duration of the larval stage it seems that the relative distribution of Odonata is not primarily associated with this stage (Harabiš and Dolny, 2010). Generally, water velocity, temperature, shading, disturbance, type of substrate, trophy, aquatic vegetation (its spatial structure and abundance) and predation risk are considered to be the most important factors shaping assemblages of Odonata larvae (Buchwald, 1992;Buss et al, 2004;Johansson et al, 2006;McCauley, 2007;Strange et al, 2007;Buczyński, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of an entire life cycle, the value of terrestrial habitats may be related to the life history of a given species. For example, we can assume that species associated with temporary habitats will tend to disperse more into the surrounding environments (McCauley 2007;Harabiš and Dolný 2011), and consequently, utilize significantly more resources situated in surrounding habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Significant effects on such behaviors may be territoriality and several other densitydependent mechanisms (Harabiš and Dolný 2011). Population densities in terrestrial habitats may be significantly higher in territorial species than in non-territorial species because individuals with less competitive abilities are being forced to move into the surrounding habitats (Corbet 1999;Suhonen et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The rate of intraguild predation and especially the rate of intraguild competition vary significantly through the season (Wissinger 1989;Crowley and Johnson 1992;Hooper et al 1996). The course of life cycle and lengths of particular developmental stages characteristic for the genus Sympecma are to some extent 'inverse' relative to other temperate damselfly species (Harabiš and Dolný 2010). The overwintering Sympecma adults begin to be active out of water early in spring (prevernal period).…”
Section: Introductionmentioning
confidence: 99%